(untitled) (Ibrahim Medical College Journal, 2009)
Contraceptive prevalence rate (CPR) is lower while the fertility is higher among rural married women aged 15-29 in Bangladesh. Thus, this comparative study attempted to identify the socioeconomic and cultural determinants of contraceptive use in different rural settings. In this primary data based cross sectional study, a semi-structured questionnaire was applied to women aged 15-29 years in two rural areas who had at least one live birth on/before 20 December, 2006. The study areas were identified by multi-stage random sampling technique. Results showed that CPR was slightly higher in Dariadaulat (43.4%) than that of Chardigoldi union (41.6%) while the mean duration of use was slightly higher in Chardigoldi compared to Dariadaulat (5.04 v. 4.59 mo). Regression model for Dariadaulat (38.7% with P<0.001) better explained the use of contraception than that of Chardigoldi (30.0% with P<0.001). Among the determinants in Dariadaulat the most explanatory variable was mass media exposure (15.8%) while it was desired number of children in Chardigoldi (12.6%). Among others, joint decision of using contraception, familiarity with contraceptives before marriage, desired number of children, electricity, family interference and family size were found to have significant impact in Dariadaulat. On the other hand, the other explanatory variables in Chardigoldi were joint decision of using contraception, family interference and familiarity with contraceptives before marriage and age at present. It may be concluded that the CPR is markedly low in rural communities. The lack of accessibility to mass media, lack of joint decision with husband, premarital unawareness regarding contraceptive use, lack of post-marital planning and family interference are major contributory factors for the low CPR in the study population. Ibrahim Med. Coll. J. 2008; 2(2): 49-54 Key Words: Determinants, contraceptive use, marriage, first live birth, rural women doi: 10.3329/imcj.v2i2.2937